Discourse Functions of Rhetorical Devices in Selected Roman Catholic Bishops’ Pastoral Letters in Onitsha Ecclesiastical Province, Nigeria (2014)
The pastoral letter, an open letter addressed by a bishop to members of his diocese for the purpose of promoting faith and good Christian living, constitutes a persuasive religious discourse characterised by numerous rhetorical devices. Previous studies on Christian religious languagehave concentrated mainly on sermons, liturgy, prayers, theology, scriptures, hymns, and songs to the exclusion of the persuasive power of pastoral letters. This study, therefore, examined themes and rhetorical devices in selected Roman Catholic bishops‘ pastoral letters in the Onitsha Ecclesiastical Province, with a view to determining their persuasive discourse functions. Aristotelian Rhetoric, which emphasises persuasion through three main rhetorical appeals: logos,pathos,andethos was adopted as the framework.Data were drawn from 10 pastoral letters of five Roman Catholic bishops in five dioceses (two letters from each) where pastoral letters are published regularly, out of the seven in Onitsha Province. These were Onitsha, Nnewi, Awka, Enugu, and Awgudioceses. The letters, published between 2000 and 2010 and ranging between 20 and 104 pages, were purposively selected based on consistency, thematic preoccupations, and rhetorical content. Data were subjected to discourse analysis. Four major themes: faith, repentance, love, and loyalty to the Roman Catholic Church were identified. There were three categories of rhetorical devices: logos-based (logic), pathos-based (emotions), and ethos-based (character). There were 10 logos-based devices: use of testimonial reference functioning as authority to validate messages; deductive and inductive reasoningappealing to the rationality of the audience; definitions establishing a common ground for arguments; comparison (analogy/metaphor) for explanations to ensure comprehension; nominalisation and passivisation objectifying the validity of ideas; syntactic parallelism and antithesis emphasising ideas for easy grasp; and obligation/necessity modals appealing to the audience‘s sense of responsibility and moral duty. Eight pathos-based deviceswere used: Igbo language expressing solidarity with the audience; prayersinspiring them; inclusive pronoun (we) creating a feeling of belonging, collectivism and oneness; rhetorical questions (RQs) appealing to denominational sentiments; sarcasm, segregation pronoun (they), and negative emotion-laden words referring to non- Catholic groups to create distaste for non-Catholic faith; feminine pronoun (she) and positive emotion-laden words referring to the Roman Catholic Church (RCC) to keep the audience emotionally attached to it.Finally, seven devices characterised ethos: use of firstiii person singular pronoun (I), declaratives, and imperatives invoking the authority of the bishops‘ office; Latinisms showing learnedness; greetings and appreciation expressing goodwill; and exemplary Biblical characters as models of faith, repentance, and love. All the devices in the three categories related to the four themes except RQs, the pronouns they, she, and emotion-laden words, relating to loyalty. Comparatively, logos-based devices preponderated over pathos- and ethos-based ones reflecting emphasis of the RCC on reason as the basis for faith. Roman Catholic bishops‘ pastoral letters in the Onitsha Ecclesiastical Province were characterised by a preponderance of logos-based rhetorical devices, and a widespread use of pathos- and ethos-based ones,designed to communicate messages of faith, repentance, love, and loyalty, and persuade the audience to live accordingly.The rhetorical devices, therefore, establish the pastorals as a significant form of persuasive religious discourse